1999
DOI: 10.1677/joe.0.1620331
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor gamma is induced during differentiation of colon epithelium cells

Abstract: Peroxisome proliferator-activated receptor (PPAR ), a fatty acid-activated nuclear receptor, is implicated in adipocyte differentiation and insulin sensitisation. In view of the association of dietary fat intake and bowel disease, the expression of PPAR in rodent and human intestine was studied. Expression of PPAR mRNA was examined by Northern blot hybridisation, RNase protection, and/or competitive RT-PCR assays, whereas PPAR protein levels were evaluated by immunoblotting and immunohistochemistry. PPAR mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
104
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 34 publications
9
104
0
Order By: Relevance
“…4). These results are similar to previous data obtained in vitro (2,3) or in vivo in human and rodent (4,7,23). However, the addition of GLN in the medium lowered PPARγ protein content but had no effect at mRNAs, suggesting that GLN impact may involve the regulation of receptor translation since PPARγ protein achieved similar levels when cells were grown in medium containing GLN (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…4). These results are similar to previous data obtained in vitro (2,3) or in vivo in human and rodent (4,7,23). However, the addition of GLN in the medium lowered PPARγ protein content but had no effect at mRNAs, suggesting that GLN impact may involve the regulation of receptor translation since PPARγ protein achieved similar levels when cells were grown in medium containing GLN (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…6). A cytoplasmic localisation of the receptor is associated with inactive PPARγ in several cancer samples (3,(46)(47)(48)(49). It is expected that GLN inhibits receptor translocation to the nucleus by increasing receptor phosphorylation which reduces PPARγ independent transactivation at the receptor A/B domain (50,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 PPAR␥ is a member of the superfamily of nuclear receptors and has important anti-inflammatory activity, 15,16 because it inhibits the activation of nuclear factor B (NF B) and the expression of the proinflammatory cytokines IL-1␤ and tumor necrosis factor-␣ (TNF-␣). [17][18][19] The colon expresses a high density of PPAR␥, 20,21 and much evidence points to the involvement of the PPAR␥ receptor in the regulation of intestinal inflammation. 20,22 Recently, Gertsch et al 23 demonstrated that the sesquiterpene (E)-␤-caryophyllene (BCP) selectively binds to CB2 and acts as a full agonist.…”
mentioning
confidence: 99%
“…3 In addition to adipose tissue, gastrointestinal epithelial cells express significant amounts of PPAR␥. [3][4][5] Other investigations, as well as our own, have shown that ligand activation of PPAR␥ leads to growth inhibition and induces the differentiation of colon cancer cells. 6 -8 It has been suggested that the inhibition of the DNA binding and transcriptional activity of the cell growth-promoting E2F/DP transcription factor represents 1 of the mechanisms by which PPAR␥ promotes adipogenesis.…”
mentioning
confidence: 77%